Radionuclide esophageal transit test to detect esophageal disorders in patients with mitra valve prolapse - Kao, Chia-Hung; Tsai, Shih-Chuan; Hsieh, Jih-Fang; Ho, Yung-Jen; Ding, Hueisch-Jy (Nuklearmedizin - NuclearMedicine, 2000)
Aim: The origin of chest discomfort in patients with mitral valve prolapse (MVP) is controversial. Our aim was to prospectively determine the incidence of esophageal disorders in MVP patients with or without chest pain. Methods: Twenty-five MVP patients with chest pain (group A) and 25 MVP patients without chest pain (group B) underwent evaluation of esophageal motility. None of the total of 50 MVP patients had significant coronary artery disease on cardiac catheterization. Esophageal motility including esophageal mean transit time (MTT), residual fraction (RF), and retrograde index (Rl) was analyzed by the radionuclide esophageal transit test (RETT). Results: In comparison with 25 age and sex-matched healthy volunteers, the results showed that: (1) 19 patients in group A (76%) had abnormal RETT findings (48% of cases with prolonged MTT, 44% of cases with higher RF, and 60% of cases with higher Rl); (2) 3 patients in group B (12%) had abnormal RETT findings (8% of cases with prolonged MTT, 4% of cases with higher RF, and 8% of cases with higher Rl). In addition, mean values of MTT, RF, and Rl in group A patients were significantly higher than in group B patients and healthy volunteers. Conclusion: We found that the chest pain in some MVP patients may be related to abnormal esophageal motility, based on the evidence from a simple and noninvasive RETT.
Keywords: Radionuclide esophageal transit test; mitral valve prolapse; chest pain